Congestion control and fast retransmission policies for transport layer multihoming in wireless environments - Ansay, Rafael Lean D.
A number of successful researches using insights on whether packet losses are either due to congestion or random errors has been conducted to enhance the performance of TCP congestion control in wireless networks. We apply and use these enhancements in SCTP, a congestion control based on a Reno-style TCP with selective acknowledgement, and study the effects of the enhancements to connections in multihoming mode. We implement a new fast retransmission policy which performs congestion related retransmissions using an alternate path and non-congestion related retransmission using the primary path. We show using extensive simulations that the proposed policy performs best under various scenarios when compared to existing path selection policies for multihomed SCTP.